Microsoft Access 2010 plain & simple - Frye, Curtis, 1968-; Safari eBooks (Sebastopol, Calif. : O'Reilly Media, 2010)
"With this full color, no-nonsense guide, you'll learn the quickest ways to solve a problem or learn a skill with Microsoft Access 2010. Easy-to-follow steps and concise, straightforward language make learning plain and simple!"--Resource description page.
Description based on print version record.
Keywords: Microsoft Access; Database management; Electronic books